Children on the Autism Spectrum and the Use of Virtual Reality for Supporting Social Skills - Alessandro Frolli; Giulia Savarese; Francesca Di Carmine; Antonia Bosco; Emilio Saviano; Angelo Rega; Marco Carotenuto; Maria Carla Ricci (MDPI AG, 2022)
Background: Autism spectrum disorders (ASDs) are characterized by differences in socio-pragmatic communication. These conditions are allocated within a "spectrum" of phenotypic variability. Virtual reality (VR) is a useful tool for healthcare intervention and particularly safely advancing social abilities in children with ASD. Methods: In our study two types of intervention for improving social skills were compared: (i) emotional training obtained by the use of virtual reality (Gr1), (ii) traditional emotional training performed individually with a therapist (Gr2). We aimed to identify the intervention with the shortest acquisition time for the proposed social tasks. Results: Our findings show that both types of intervention had the same acquisition time for the recognition of primary emotions. However, for the use of primary and secondary emotions, the group using VR showed shorter acquisition times. Conclusions: These findings together with previous preliminary datasuggest that VR can be a promising, dynamic and effective practice for the support of basic and complex social skills of these individuals.